Artificial Intelligence dalam Administrasi Pajak: Tinjauan Literatur Mengenai Efisiensi, Transparansi, dan Akuntabilitas - Lailatul Fadhilah; Salsabila, Savira; Aji, Gunawan (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2025)
Artificial Intelligence (AI) plays an increasingly important role in the modernization of tax administration in Indonesia. The application of AI is a key strategy for improving the efficiency, transparency, and accuracy of data management, especially amid the increasing complexity of transactions and the demand for fast and responsive tax services. Traditional tax administration faces challenges such as the limitations of manual analysis, potential recording errors, and weak detection of non-compliance. This study aims to analyze the role of AI in improving the quality of tax administration as well as examine the challenges that emerge during its implementation. This study adopts a literature review method supported by a descriptive qualitative approach. The results show that AI can strengthen process automation, improve data analysis accuracy, support risk-based audits, and improve overall taxation system oversight. However, AI implementation still faces challenges in the form of data security, algorithmic bias risks, and limitations in digital infrastructure that must be improved for its optimal utilization.